Dampak Parkir On-Street Terhadap Arus Lalu Lintas (Studi Kasus: Taman Singha dan Taman Bunga Merjosari, Jl. Mertojoyo, Kota Malang) - Arminia Supa Balu Meru; M. Sadillah; Andy Kristafi Arifianto (Prosiding SENTIKUIN (Seminar Nasional Teknologi Industri, Lingkungan dan Infrastruktur), 2025)
This study aims to examine the impact of on-street parking on traffic flow performance in the Singha Park and Merjosari Flower Garden areas of Malang City. On-street parking is an urban transportation problem that has the potential to reduce road capacity and disrupt traffic flow. This study uses a quantitative approach with a field survey method that refers to the 2023 Indonesian Road Capacity Guidelines (PKJI). The data collected includes traffic volume, road capacity, degree of saturation, road service level, and parking characteristics, including the availability and demand for parking spaces. The results show that parking on the road significantly reduces the effective capacity of vehicle lanes, increases side obstacles, and reduces traffic flow performance, especially during rush hour. At the research location, there are 26 motorcycle parking spaces with a parking waiting time of between five and six minutes. However, the demand for parking spaces exceeds the number of available spaces, putting pressure on traffic performance. Road performance analysis shows that the service level is in category C with a saturation degree of 0.53, indicating that traffic flow is still relatively stable but disruptions are beginning to be felt by road users. The highest number of side obstructions recorded was 1,188 incidents on Saturday. In addition, the modeling results show that removing parking spaces on the road has the potential to increase road capacity and reduce traffic congestion. These findings emphasize the importance of implementing effective and sustainable parking management strategies to improve traffic performance, comfort, and safety for road users in high-activity urban areas, especially urban recreational areas with high visitor traffic.